Germination and growth control in ornamental sunflower grown under photoconverter screen using different doses of gibberellic acid - de Luna, Kauan Augusto Ceriani [UNESP]; da Silva, Rúbio Vinicius Gomes [UNESP]; Ribeiro, Nathalia Aparecida [UNESP]; Fabrino, Franco Monici [UNESP]; Freitas, Pâmela Gomes Nakada [UNESP]; de Soutello, Ricardo Velludo Gomes [UNESP]; Rodrigues, Maria Gabriela Fontanetti [UNESP] (Universidade Estadual de Londrina, 2025)
Helianthus annuus L., commonly known as the dwarf sunflower, has become popular in the ornamental flower market in Brazil, increasing its demand in floriculture retail. It is one of the most commercialized flowers. In addition to its unique characteristics, such as its inflorescence and vibrant petal color, it is a hardy plant that adapts to the different environments. However, excessive sunlight can harm its floral composition, affecting its appearance and marketability. Various management strategies have been adopted to achieve adequate productivity and meet market demands. These strategies include applying gibberellic acid to increase seed germination, and using photoconverter screens to minimize sunlight-induced damage to petals by altering light spectrum and intensity and converting direct radiation into diffuse radiation without impairing plant development and photosynthesis. Two consecutive experiments were conducted in this study. The first aimed to determine the optimal gibberellic acid dose by observing the germination speed index, and quantifying normal and abnormal seedlings. Four different doses (0, 100, 250, and 500 mg L−1 of gibberellic acid) were tested with four replicates. The second experiment aimed to verify the ideal color of photoconverter screen by comparing three treatments, including the control (without using photoconverter screens), a red photoconverter screen, and a silver photoconverter screen. Ten replicates were used, assessing agronomic traits essential for the commercial value of plants, such as plant height, stem diameter and length, root length, and relative growth rate of the plant. The experiments were conducted in the municipality of Dracena, São Paulo, Brazil. The first experiment was performed in a completely randomized design, while the second in a randomized block design, in a greenhouse with automatic irrigation. The results indicated that for dwarf sunflower seeds, the optimal dose of gibberellic acid was 500 mg L−1, which achieved 100% germination after seven days and significantly differed from the lower doses for normal plants and plant length. This optimal dose was used in seed treatment for the second experiment. The results revealed that the use of both red and silver photoconverter screens improved the development of plants, increasing their height, stem diameter, and stem length, fundamental traits required for their commercialization, while improving the development and relative growth rate.
Germinação e controle do crescimento de girassol ornamental cultivado em tela fotoconversora utilizando diferentes doses de ácido giberélico
Keywords: Dwarf sunflower; Helianthus annuus L; Potted Flowers; Vegetable regulator